Detection of bcr-abl Fusion Gene Expression in Chronic Myelogenous - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Leukemia is hematology malignancy caused by excess proliferation of hematopoetic or lymphoid cells. Leukemia cases in Indonesia were about 3,7 per 100.000 with mortality rate 83,6% and diagnosed based on FAB classification. The fact, WHO classification 2000, used worldwide based on cytogenesis and molecular biology profile, can define the clonal diseases more precisely and to choose the adequate therapy. CML case is about 15% of all adult leukemia cases and most of the cases are related with t(9